Man uttered by God - Godawa, Marcin (Bogoslovni vestnik, 2023)
In search of understanding of a human being throughout the history, from the perspective of Christian spiritual theology contemplation should be especially highlighted. The contemplative capacity (vita contemplativa) renders the inmost reality of a man. The analysis of Thomas Merton’s work New Seeds of Contemplation portrays contemplation as “the highest expression of man’s intellectual and spiritual life” (Merton 1961, 1) and wholly personal identity of a human. The aim of this article is to present the personal essence of contemplation. The content, arrived at by use of tools of spiritual theology, shows the interpersonal essence of contemplation, where the concept of the true self (spiritus) is especially emphasised. It will be explained by Merton’s apprehension of a man as “God’s utterance” and as a personal contemplative response to Him. Finally, some correlations between the personal contemplation and contemporary thought (Levinas, Marion, Luckmann, Rosa) will be pointed out to suggest the vital productivity of Christian experience.
Keywords: Bog; contemplation; človek; dialog; dialogue; fenomenologija; God; kontemplacija; man; Merton, Thomas; oseba; person; phenomenology; resnični jaz; true self